EUROPEAN ECONOMETRIC ANALYSIS OF THE INTERCONNECTION OF CONSUMPTION AND GDP APPROACHED ACCORDING TO EVIEWS PROGRAM - ANA PETRINA STANCIU; NADIA ELENA STOICUŢA (Annals of the University of Petrosani: Economics)
The hereby paper deals with an econometric analysis of the interconnection of consumption per capita and GDP within 27 European Union member states during a three years’ period. The main purpose of the paper is to show the manner Eviews program is able to handle such an approach, the stages to be followed as well as the carrying out of certain previsions.